Empowerment And Job Satisfaction On Personnel Performance: Organizational Commitment As Moderator - Jabrudin (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
This explanatory quantitative research aims to test the model of the empirical causality relationship between empowerment, job satisfaction, organizational commitment, and personnel performance within the Directorate of Criminal Investigation of the Southeast Sulawesi Police. Using Structural Equation Modeling - Partial Least Squares (SEM-PLS) analysis of data collected through a structured questionnaire, this study reveals that empowerment plays a central role because it is proven to be able to improve operational performance directly as well as being the main driver of drastic improvements in personnel job satisfaction. Furthermore, high job satisfaction was identified as having a strong positive impact in spurring the achievement of investigation performance in the field. Another crucial finding suggests that although organizational commitment independently does not exert a significant direct influence on performance improvement, it serves effectively as an important moderator that reinforces the positive relationship between empowerment and personnel performance. Thus, this study concludes that optimizing the operational performance of the police cannot rely solely on loyalty, but requires a delegation of authority strategy supported by job satisfaction and strengthened by organizational commitment as a catalyst.